(x + 3)(3x - 2)
I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?
15x minus 8=minus 180 3x+8=24
the answer is -174
This simplifies to 3x-6+4y.
Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.Assuming there should have been a plus or minus sign between 4x2and 3x, the answer is: a binomial.
x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)
(x + 3)(3x - 2)
3x - 5x + x = -x
I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?
15x minus 8=minus 180 3x+8=24
the answer is -174
This simplifies to 3x-6+4y.
(x + 2)(3x - 1)(3x + 1)
(3x-2)(x-2)
Because (x plus 3x) is 4x, and (-5 + 11) is 6.
3x - 12 = 10x - 15 - 6x -10 3x - 12 = 4x -25 3x + 13 = 4x 13 = 4x - 3x 13 = x None?